Annual physical examination, is it valuable? Reasons for non-utilization among the constituents of the University of the Philippines Health Service, Diliman Quezon City - Alip, Myrissa Melinda Lacuna
Background: The Annual physical examination package of the University of Health Service, Diliman campus is a privilege that personnel are entitled to. Through the years though, there is a low-utilization of the said service. There is a need to explore the reasons for the non-utilization and subsequently arrive at strategies to address this. Objective: To determine the reasons for non-utilization of the Annual Medical Examination of the UPHS Diliman by faculty, REPS and employees and identify possible barriers that can be corrected. Methods: This is a descriptive cross-sectional study using survey questionnaire. Included in the study were the employees, REPS and faculty of the University of the Philippines, Diliman campus. Purposive sampling method was used. Data collected were encoded and analyzed using the EpiInfo 6 software. Recommendations and additional comments of the respondents were then collated. Results: Of the 534 respondents, majority were females (61.2%); mean age was 45±11; 60% were employees; 55% were college graduates; 84% were aware of the APE; 57% utilized the service; absence of free time was the primary reason for non-utilization. Conclusion: The factor that was cited as the primary reason for non-utilization was ?lack of time?, followed by, ?not allowed by the office,? and ?PE done outside.?
Management study (MHA)--University of the Philippines Manila, 2013
Keywords: Physical Examination